Influencia de pre tratamientos convencionales en el proceso de secado de piña y en las características físicas del producto final - Buestán, Enrique (2010)
The Aim in the investigation was to evaluate the effect of different pre-treatments as osmotic dehydration, use of antioxidant and scalded in the pineapple after the dried one. Once finished the dried one of the different pre-treatments isotherms developed, in order to determine the value of the monocaps, which are intimately related to the useful life of the product. Another side, the speed was analyzed of dried of the fruits, whit that was possible to observe that the product with major speed of dried was the one that did not suffer any pre-treatment, and this is relates to the useful life. To complete the investigation the useful life of the pineapple decided by means of the method described by Theodore Labuza. In conclusion of this study the information obtained with the isotherms was corroborated and the approximate time of useful life of the same ones. The observed results demonstrated that the product with major useful life was the one that did not suffer any pre treatment before the dried one. All the results were analyzed statistically an experimental design, in order to compare the variables of answers obtained during the development of the project with a degree of significancia of 95 %.